(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In the todays Communication world, mobile and its applications are the most emerging trends. Mobile applications are the exact replacements of web based applications. Based on this statistics we are planning to migrate web based application of college library to mobile application. In most of the college website we see applications like latest news, Attendance, Login and Registrations, EBooks, Forums, Results, Chat application, Web Mail, etc.. Based on the same we would to do the same thing in a mobile application. The reason behind the work is that the mobile applications do not need any third party browsers, or they don’t need any domain registration. So in order to take the advantages of all this limitations we are planning to develop the mobile applications. Now the main important modules that I want to implement on my mobile application is OPAC (Online Public Access Catalogue) for a library account. Using OPAC mechanism in mobile one can just access the library account of his/her from anywhere using his mobile device, So that they can check the availability of books in the library instead of going to library. They can even check the number of books that are taken in there account and its submission date, fine to be paid in case.